Viral etiology of encephalitis in children in southern Vietnam: results of a one-year prospective descriptive study. - Van Tan Le; Tu Qui Phan; Quang Ha Do; Bach Hue Nguyen; Quoi Bao Lam; Van Cam Bach; Huu Khanh Truong; Tinh Hien Tran; Van Vinh Chau Nguyen; Tan Tram Tran; Minh Hien Vo; Vu Thieu Nga Tran; et al. (Public Library of Science (PLoS), 2010)
Acute encephalitis is an important and severe disease in children in Vietnam. However, little is known about the etiology while such knowledge is essential for optimal prevention and treatment. To identify viral causes of encephalitis, in 2004 we conducted a one-year descriptive study at Children's Hospital Number One, a referral hospital for children in southern Vietnam including Ho Chi Minh City.Children less than 16 years of age presenting with acute encephalitis of presumed viral etiology were enrolled. Diagnostic efforts included viral culture, serology and real time (RT)-PCRs. A confirmed or probable viral causative agent was established in 41% of 194 enrolled patients. The most commonly diagnosed causative agent was Japanese encephalitis virus (n = 50, 26%), followed by enteroviruses (n = 18, 9.3%), dengue virus (n = 9, 4.6%), herpes simplex virus (n = 1), cytomegalovirus (n = 1) and influenza A virus (n = 1). Fifty-seven (29%) children died acutely. Fatal outcome was independently associated with patient age and Glasgow Coma Scale (GCS) on admission.Acute encephalitis in children in southern Vietnam is associated with high mortality. Although the etiology remains unknown in a majority of the patients, the result from the present study may be useful for future design of treatment and prevention strategies of the disease. The recognition of GCS and age as predictive factors may be helpful for clinicians in managing the patient.